PERFORMANCE OF AGRIBUSINESS COMPANIES - WHAT KIND OF GOVERNING STRUCTURE SHOULD WE ADOPT? - Ina Pagria; Bahri Musabelliu; Denisa Pipero (European Scientific Journal, ESJ, 2012)
It is already known the fact that the performance of an enterprise is the result of good or bad management. But when we talk about "management" often we overlook, or even worse, we don’t consider such problems associated with the growth strategies of companies, which normally derive from the forms of governance. Surveys made so far lead us to conclude that the actual performance of a large number of enterprises, engaged in various agribusiness industries is highly associated with both the issues mentioned above, and therefore they are the focus of this study. Our goal is that by the conclusions drawn in this paper, can be offered recommendations on growth strategies that enterprises should implement, and more rational governance forms according to industries.